Hesperidin alleviates vascular dysfunction and remodelling in high-fat/high-fructose diet-fed rats by modulating oxidative stress, inflammation, AdipoR1, and eNOS expression. (October 2022) - Apaijit, Kwanjit; Pakdeechote, Poungrat; Maneesai, Putcharawipa; Meephat, Sariya; Prasatthong, Patoomporn; Bunbupha, Sarawoot
Abstract: Hesperidin, a flavanone glycoside, has shown antihypertensive, antioxidant, and anti-inflammatory effects. In the present study, the therapeutic effects of hesperidin on vascular function and remodelling, and possible underlying mechanisms involved in high-fat/high-fructose diet (HFFD)-fed rats were investigated. Male Sprague-Dawley rats were fed a high-fat diet plus 15% fructose in drinking water for 16 weeks. HFFD-fed rats were treated with hesperidin (30 mg/kg/day) or vehicle for the last 4 weeks. Treatment of HFFD-fed rats with hesperidin significantly attenuated metabolic alterations, vascular endothelial dysfunction and remodelling. Hesperidin markedly alleviated HFFD-induced oxidative stress and inflammation by decreasing plasma malondialdehyde level and aortic superoxide anion production, and by suppressing aortic tumor necrosis factor-α and interleukin-6 overexpression. Additionally, increased plasma levels of the adiponectin and nitric oxide metabolite, together with restoration of adiponectin receptor 1 (AdipoR1) and endothelial nitric oxide synthase (eNOS) protein expression, were also observed after treatment with hesperidin. These findings indicated that hesperidin alleviates HFFD-induced vascular dysfunction and remodelling in rats. The possible underlying mechanism may involve the reduction of oxidative stress and inflammation, and the restoration of AdipoR1and eNOS expression. Highlights: Hesperidin alleviated high-fat/high-fructose diet-induced insulin resistance, dyslipidemia, and hypertension. Hesperidin alleviated high-fat/high-fructose diet-induced vascular endothelial dysfunction and remodelling. Hesperidin exhibited antioxidant property by suppressing the lipid peroxidation level and O2 − production. Hesperidin exhibited anti-inflammatory property by suppressing the expression of TNF-α and IL-6. Hesperidin enhanced protein AdipoR1 and eNOS expression.